Disordered quantum Hall ferromagnets and cooperative transport anisotropy - Chalker, J; Polyakov, D; Evers, F; Mirlin, A; Wolfle, P (2004)
We discuss the behaviour of a quantum Hall system when two Landau levels with opposite spin and combined filling factor near unity are brought into energetic coincidence using an in-plane component of magnetic field. We focus on the interpretation of recent experiments under these conditions (Phys. Rev. Lett. 86 (2001) 866; Phys. Rev. B 64 (2001) 121305), in which a large resistance anisotropy develops at low temperatures. Modelling the systems involved as Ising quantum Hall ferromagnets, we suggest that this transport anisotropy reflects domain formation induced by a random field arising from isotropic sample surface roughness. (C) 2003 Elsevier B.V. All rights reserved.